The Effect of Using Instructional Videos to Improve Bustier Pattern-Making Skills Among Fashion Design and Business Students at Ciputra University, Surabaya - Soelistyowati Soelistyowati; Hutomo Setia Budi (International Journal Labs, 2026)
Digital transformation has driven innovation in practical learning media, particularly in supporting the acquisition of complex skills. Instructional video has emerged as an effective solution for enhancing practice-based learning. This study aims to analyze the effect of instructional video utilization on students’ skills in bustier pattern making within the Fashion Design and Business program at Universitas Ciputra Surabaya. The research sample consisted of students divided into an experimental group and a control group using purposive sampling techniques. A quantitative approach was employed, utilizing a quasi-experimental method with a pretest–posttest control group design. Data were collected through practical tests and skill assessment rubrics, and subsequently analyzed using descriptive statistics and an independent sample t-test. The results indicate a significant difference between the experimental and control groups, with a significance value of 0.000 (<0.05), demonstrating that the use of instructional videos effectively improves students’ bustier pattern-making skills. Students in the experimental group achieved higher performance outcomes compared to those in the control group. In conclusion, instructional video has a significant and effective impact as a practical learning medium in teaching bustier pattern making in fashion design education